A Facile Synthesis Method to Obtain SrSnO3@AO2 (A = Ti or Zr) Core Shell Systems - L. Lucena, Guilherme; da S. Maia, Ary; Longo, Elson; G. de Souza, Antonio; M. G. dos Santos, Ieda (Current Physical Chemistry, 2015)
SrSnO3@TiO2 and SrSnO3@ZrO2 core-shell nanoparticles were synthesized using the modified-Pechini method by impregnating the shell material on commercial materials (core) using a polymeric resin. The formation of SrSnO3 on TiO2 was confirmed by Xray diffraction and infrared spectroscopy, while superposition with ZrO peaks/bands occurred making this evaluation more difficult. Micrographs obtained using field emission scanning electron microscopy and transmission electron microscopy confirmed the dispersion of the perovskite phase on TiO2 and on ZrO2. The methodology applied in this study is promising in the synthesis of core@shell systems, using water as solvent and a low heat treatment temperature.
Keywords: Core@shell